Cession de créances et affacturage - Demers, Robert (Les Cahiers de droit, 1980)
Credit factoring has become over the years an important method of obtaining capital and adequate financing for medium size business. Although factoring imports a special relationship between the factor and his client, it is essential to keep in mind that the relationship with third parties is governed in such cases by the general rules of the Civil Code on assignment of book debts. The Faucher case discussed herein illustrates the applicability to factoring situations of the rules embodied in article 1571d) of the Civil Code.